Retracing Baptists in Rhode Island: Identity, Formation, and History. - Lemons, J. Stanley (Baylor University Press, 2019)
Cover -- Full Blurbs, Title Page, Copyright -- Contents -- Acknowledgments -- Introduction -- Part I. Awakenings -- 1. Baptist Beginnings -- 2. Sixes &amp -- Sevens and Musical Discord -- 3. The Rise of the Regular Baptists -- 4. Calvinism Challenged -- Part II. Transformations -- 5. The Freewill Baptists -- 6. Contested Ground -- 7. Missions and Sunday Schools -- 8. Trials and Tribulations -- Part III. Divisions -- 9. Freemasons and Dorrites -- 10. Slavery, Race, and Antislavery -- 11. Rum, Romanism, and Americanization -- 12. Brown University and the Baptists -- 13. Wars of Religion -- Part IV. Remakings -- 14. Revivals and Revivalists -- 15. The Daughters of Eve and the Better Half -- 16. Tides of Change -- 17. The Changing Mainline -- Notes -- Bibliography -- Index.